2017
DOI: 10.15252/embr.201643827
|View full text |Cite
|
Sign up to set email alerts
|

Mfn2 deletion in brown adipose tissue protects from insulin resistance and impairs thermogenesis

Abstract: BAT‐controlled thermogenic activity is thought to be required for its capacity to prevent the development of insulin resistance. This hypothesis predicts that mediators of thermogenesis may help prevent diet‐induced insulin resistance. We report that the mitochondrial fusion protein Mitofusin 2 (Mfn2) in BAT is essential for cold‐stimulated thermogenesis, but promotes insulin resistance in obese mice. Mfn2 deletion in mice through Ucp1‐cre (BAT‐Mfn2‐KO) causes BAT lipohypertrophy and cold intolerance. Surprisi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
92
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
3
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 97 publications
(97 citation statements)
references
References 25 publications
4
92
0
1
Order By: Relevance
“…Mfn2 ablation in adipose tissues obtained by crossing Mfn2 loxP/loxP mice with mice expressing the Cre recombinase under the adiponectin promoter leads to enhanced body weight and fat mass, which was linked to a reduction in energy expenditure and in BAT thermogenesis [3]. In keeping with these data, BAT-specific Mfn2 deletion through Ucp1-Cre causes BAT lipohypertrophy and cold intolerance [169]. The effects linked to Mfn2 ablation in adipose depots are not detected upon ablation of Mfn1 [3].…”
Section: Metabolic Impact Of Alterations In Proteins Participating Inmentioning
confidence: 76%
“…Mfn2 ablation in adipose tissues obtained by crossing Mfn2 loxP/loxP mice with mice expressing the Cre recombinase under the adiponectin promoter leads to enhanced body weight and fat mass, which was linked to a reduction in energy expenditure and in BAT thermogenesis [3]. In keeping with these data, BAT-specific Mfn2 deletion through Ucp1-Cre causes BAT lipohypertrophy and cold intolerance [169]. The effects linked to Mfn2 ablation in adipose depots are not detected upon ablation of Mfn1 [3].…”
Section: Metabolic Impact Of Alterations In Proteins Participating Inmentioning
confidence: 76%
“…While both studies do not present the effects of an adipose tissue‐specific ClpP knock out, the results shown suggest that ClpP deletion within adipose tissue, and not in other tissues, is responsible for the mitochondrial changes in WAT and brown adipose tissue (BAT). Our rationale behind this conclusion is that BAT and WAT remodeling in ClpP KO mice resemble the effects of BAT‐specific deletion of the mitochondrial quality control and fusion protein, mitofusin 2 (Mfn2) . Becker et al showed that ClpP KO BAT is hypertrophied, accumulates more lipids, and reduces Ucp1 expression in chow diet‐fed mice, as reported in BAT‐specific Mfn2 knockout (BAT‐Mfn2 KO) mice.…”
Section: The Role Of the Mitochondrial Protease Clpp In Obesity And Imentioning
confidence: 90%
“…Indeed, ablation of Mfn2 specifically in the liver promotes glucose intolerance and enhanced hepatic gluconeogenesis [7], while Mfn2 deficiency in hypothalamic POMC neurons leads to decreased energy expenditure and hyperphagia, resulting in an obese phenotype [8]. In combination with the two current reports by Boutant et al and Mahdaviani et al, the combined data suggest Mfn2 to play a rather protective role against non-favorable metabolic conditions across a number of distinct organ compartments [1,2]. In this scenario, the reported elevated levels of Mfn2 in BAT of high fat diet-fed mice [1] could be interpreted as a rather counterregulatory consequence toward excessive caloric intake.…”
mentioning
confidence: 81%
“…Despite these important but still unresolved issues, the studies by Boutant et al and Mahdaviani et al help us to make a number of general conclusions for future BAT research [1,2]. It becomes obvious that an enhancement of mitochondrial fission is probably not sufficient to promote uncoupling potential, despite earlier findings that mitochondrial fission is needed to increase brown adipocyte energy dissipation [9].…”
mentioning
confidence: 99%